Airport Development Planning (Case Study: Mozes Kilangin International Airport) - Amri, Salsabila Miyazumi; Pagarsukma, Muhammad Azhan (Universitas Pendidikan Indonesia (UPI), 2021)
The aim of this research is to calculating the volume requirements for runways, taxiways and aprons in future conditions based on the planned aircraft CN-235 type. In planning the development of an airport, one must estimate the traffic flow in the future. Therefore, this paper is based on research results. By analyzing the five-year data on the number of aircraft, passengers, luggage and cargo using regression analysis, it can be predicted that the traffic flow in the future so that airport development can be determined whether it is necessary to do or not. Based on primary data obtained from airports such as climatological data, aircraft characteristics data, land data, and existing airport data, it is used as a reference for planning airport development. Based on the results of calculations that refer to the standards of the International Civil Aviation Organization (ICAO) with the CN-235 plan aircraft, it takes a runway length of 3,949 meters and a runway width of 60 meters.Â The distance between the runway axis and the runway axis is 185 meters. The total width of the taxiway is 38 meters, and the required apron area is 750.5 Ã— 164 = 123,082 m. Benefit of the Research is as material to consider for evaluating the function of airports in support of faster mobilization in the future